Kesulitan Mahasiswa Tahun Masuk 2018 dalam Memahami Teks Bahasa Jepang - Hanifah Nurulhuda; Damai Yani (Omiyage : Jurnal Bahasa dan Pembelajaran Bahasa Jepang, 2021)
In learning Japanese, understanding Japanese text is included in the Dokkai course. Dokkai is one of the compulsory courses that students of the Japanese language education study program, Padang State University, have to take for approximately 3 years or 6 semesters. The Japanese text does not use romaji letters, but uses 3 different types of letters, namely hiragana, katakana and kanji which make Japanese text difficult to understand. The large number of Japanese language education study program students in 2018 experienced difficulties in understanding Japanese language texts. The purpose of this study is to describe the difficulties of students in understanding Japanese text. This research is a quantitative descriptive study. The sample used in the study was 39 students. The data collection technique in this study used a questionnaire and used a Likert scale formula. While the data analysis technique is descriptive with a percentage. The results of this study found the difficulties experienced by students, among others, the sub-indicator of kanji with a percentage of 74.35%. In the linguistic indicator, students have difficulty with the vocabulary sub-indicator with a percentage of 63.7%, sentence patterns with a percentage of 64% and meaning with a percentage of 61.7%. Then in the indicator of student spelling and sound patterns, only difficulty in the sub-indicator voicing/intonation in reading with a percentage of 63.6%.